Bronchoscopic Resolution of Refractory Atelectasis in a Toddler with Polymicrobial MDR Pneumonia: A Case Report - I Wayan Sucipta; Eka Putra Setiawan; Komang Andi Dwi Saputra; Freddy Stanza Purba (HM Publisher, 2026)
Pediatric acute respiratory distress syndrome (PARDS) complicated by ventilator-associated pneumonia (VAP) poses significant management challenges, particularly when caused by multidrug-resistant organisms such as Stenotrophomonas maltophilia and Pseudomonas aeruginosa. A frequent and deleterious complication is plate-like atelectasis, which may prove refractory to conservative management due to anatomical constraints in the pediatric airway and biofilm formation. A 23-month-old male presented with severe PARDS and polymicrobial VAP. Despite extubation to High-Flow Nasal Cannula (HFNC), the patient developed persistent right upper lobe plate-like atelectasis refractory to aggressive physiotherapy and targeted antibiotic therapy with Levofloxacin and Ceftazidime for 21 days. On Day 75 of illness, a flexible bronchoscopy was performed. Intraoperative findings revealed hyperemic mucosa without macroscopic mucus plugging. However, the procedure, involving saline lavage and suctioning, resulted in immediate recruitment. Within 24 hours, the respiratory rate decreased from 45 to 24 breaths per minute, and the SpO2/FiO2 ratio improved significantly from 185 to 310, allowing weaning from respiratory support. In conclusion, in toddlers with multidrug-resistant VAP, atelectasis may persist due to biofilm-mediated micro-obstruction rather than macroscopic plugging. Flexible bronchoscopy is a safe and effective therapeutic adjunct in these cases, facilitating distal airway recruitment and breaking the cycle of chronic infection.